Understanding the genetic architecture of resistance to northern corn leaf blight and southern corn rust in maize (Zea mays L.) - Ranganatha, H. M.; Lohithaswa, H. C.; Pandravada, Anand S. (The Indian Journal of Genetics and Plant Breeding, 2017)
Among various foliar diseases, northern corn leaf blight (NCLB) incited by Exserohilum turcicum (Pass) Leonard and Suggs and southern corn rust (SCR) caused by Puccinia polysora (Underwood) are the most persistent and destructive biotic constraints in India and worldwide. The present investigation was conducted to understand the genetics of resistance to both diseases through six generation means and variances in two crosses developed by crossing two elite NCLB and SCR susceptible inbreds (CM212 and HKI162) with a common resistant inbred SKV50. Six generations of the two crosses (CM212 × SKV50 and HKI162 × SKV50) were evaluated in the disease screening nurseries for NCLB and SCR resistance at hot spot location during post rainy season of 2012 and 2013. The scaling tests and joint scaling tests indicated the inadequacy of additive-dominance model and showed the presence of epistatic gene effects in both the crosses for NCLB and SCR resistance. Study further revealed the importance of additive, dominance and additive × additive gene effects in the expression of NCLB and SCR. Duplicate gene interaction was evident in the inheritance of NCLB and SCR resistance in both the crosses. The study also revealed that genetic architecture of NCLB and SCR resistance was population specific. Both, additive and non-additive components were found important thus reciprocal recurrent selection would be more effective in developing NCLB and SCR resistant maize genotypes.